2000
DOI: 10.1136/jech.54.11.851
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer hypothesis: a single cause for the majority of cases

Abstract: Study objective-The main cause of breast cancer remains unknown. Numerous causal factors or predisposing conditions have been proposed, but account for only a small percentage of the total disease. The current search for multiple causes is unavailing. This report explores whether any single aetiological agent may be responsible for the majority of cases, and attempts to define its properties. Methods-Examination of all relevant epidemiological and biological evidence. Main results-Genetic inheritance is not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Chlebowski (2003) 1.24 1.01-1.54 migration into other social or lifestyle environments. Nonetheless, some studies of high risk families have demonstrated an impact on the occurrence of breast cancer and an interaction with hormone use at least in first degree relatives (Wiseman, 2000). Moreover, it has been suggested that the population-attributable risk of factors such as education, family history as well as individual reproductive and hormonal factors may explain up to 50% of the breast cancer riskeven if external hormone use is not considered (Henderson and Bernstein, 1996).…”
Section: Epidemiology and Risk Factors Of Conditions Affecting Post-mmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlebowski (2003) 1.24 1.01-1.54 migration into other social or lifestyle environments. Nonetheless, some studies of high risk families have demonstrated an impact on the occurrence of breast cancer and an interaction with hormone use at least in first degree relatives (Wiseman, 2000). Moreover, it has been suggested that the population-attributable risk of factors such as education, family history as well as individual reproductive and hormonal factors may explain up to 50% of the breast cancer riskeven if external hormone use is not considered (Henderson and Bernstein, 1996).…”
Section: Epidemiology and Risk Factors Of Conditions Affecting Post-mmentioning
confidence: 99%
“…The exact pathogenetic mechanisms of breast cancer initiation and/or promotion are still poorly understood (Olsson et al, 1996;Adami et al, 1998;Hofseth et al, 1999;Li et al, 2000;Wiseman, 2000;Brekelmans, 2003). Therefore, no firm causal conclusions can be established from the associations found between risk factors, including hormone use, and breast cancer.…”
Section: Dynamics Of Proliferative Breast Diseasementioning
confidence: 99%
“…Dynamics of breast cancer initiation and promotion is still poorly understood [13,[94][95][96][97]. Thus, firm causal conclusions cannot be established from the associations between hormone treatment and breast cancer found on inhomogeneous female populations.…”
Section: Dynamics Of Cancer Growth and Length Of The Observational Pementioning
confidence: 94%
“…Whereas numerous Classical Risk Factors are statistically linked to breast cancer, in fact they account for only a small proportion of the total disease. Here we deal with a factor, hypervascularity, which may be on the final common path to cancer (Wiseman, 2000). It has screening potential (Simpson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%